2008
DOI: 10.1007/s10934-008-9241-8
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic activity of mesoporous catalysts in Friedel–Crafts benzylation of benzene

Abstract: Different samples of metal-incorporated MCM-41 were prepared and used as catalysts in Friedel-Craft's benzylation of benzene. The catalytic performance was evaluated by off-line GC analysis. Fe-MCM-41 exhibited excellent activity, the sample with Si/Fe ratio = 10 showed 90% conversion with 95% selectivity towards diphenylmethane within a few minutes. Generally, the activity per Fe-site was an order of magnitude higher for the samples containing a combination of Fe 2 O 3 nano-particles and isolated Fe 3+ sites.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…It was reported that Fe-MCM-41 (ref. 35) exhibited 90% conversion of benzyl chloride with 95% selectivity towards diphenylmethane; however, this catalyst has a major disadvantage that almost 33% of the iron atoms have been removed from the framework of MCM-41 during reaction cycles. Sun et al 36 reported that 10 wt% iron oxide loaded SBA-15 catalyst showed 100% conversion of benzyl chloride aer a reaction time of 30 min and 15 wt% iron oxide loaded SBA-15 gave 100% conversion aer are action time of 45 min.…”
Section: Benzylation Of Benzenementioning
confidence: 99%
“…It was reported that Fe-MCM-41 (ref. 35) exhibited 90% conversion of benzyl chloride with 95% selectivity towards diphenylmethane; however, this catalyst has a major disadvantage that almost 33% of the iron atoms have been removed from the framework of MCM-41 during reaction cycles. Sun et al 36 reported that 10 wt% iron oxide loaded SBA-15 catalyst showed 100% conversion of benzyl chloride aer a reaction time of 30 min and 15 wt% iron oxide loaded SBA-15 gave 100% conversion aer are action time of 45 min.…”
Section: Benzylation Of Benzenementioning
confidence: 99%
“…It is however possible that catalytically inactive Fe species leach, as has been observed for the mesoporous Fe-containing silica materials. 45,46 To exclude this possibility, elemental analysis of the catalyst aer reaction was performed. For Fe 2 O 3 -ZSM-5, the Si/Fe ratio increased from 194 before reaction to 283 aer reaction, indicating that around 30% of the Fe has leached.…”
Section: Acidity Characterizationmentioning
confidence: 99%
“…In recent years, mesoporous silica materials emerged as ideal catalyst supports because of their high surface area, which have been considered to be favorable for the dispersion of Fe-containing sites [2,9,11,[18][19][20][21][22][23][24][25][26]. As expected, these Fe-containing mesoporous silica materials are very active for Friedel-Crafts type benzylation.…”
Section: Introductionmentioning
confidence: 76%